POLLUTION CONTROL AND PESTICIDES - Boltaeva K.SH (TADQIQOTLAR.UZ, 2024)
Abstract: When making CFF nitrogen consumption of soil resources in the year of  its  operation  increases  in  the  second  year  (aftereffects)  decreases  unproductive nitrogen  losses  from  CFF  markedly  lower  than  urea.  CFF  raises  productivity Artemisia leucodes Schrenk. In field experiments, conducted in the irrigated typical gray soils and debris, the harvest was bigger by 10-30% compared to the control. The research  results  point  to  a  definite  advantage  of  using  a  slow  acting    carbamide-formaldehyde  fertilizers  (CFF)  than  urea  and  ammonium  nitrate  in  reducing environmental pollution harmful to the body remains of the fat It  was  found  that  the  use  of  slow  acting  .  Urea-formaldehyde  fertilizer  is particularly important in conditions of saline soils with shallow groundwater where significant  nitrogen  losses  occur  as  a  result  of  leaching  of  nitrates  into  the groundwater. It was revealed that a higher content of nitrates in the soil when making nitrogen fertilizer as ammonium nitrate and urea lead to a significant loss of battery sizes that reach  considerable  values.  As  a  result,  there  are  a  number  of  issues  surrounding pollution as the most dangerous are increasingly finding the nitrates in the soil. It should be noted that not only accumulate nitrate in the soil - soil, ground water, but higher than allowable standards accumulate in food and feed, thus enters the body of animals and humans